America at the ballot box : elections and political history - Zelizer, Julian E.; Davies, Gareth, 1965- (Politics and culture in modern America., 2015)
Elections are, and always have been, the lifeblood of American democracy. Often raucous and sharply contentious, sometimes featuring grand debates about the nation's future, and invariably full of dramatic moments, elections offer insight into the character and historical evolution of American politics. America at the Ballot Box uses the history of presidential elections to illuminate American political democracy and its development from the early Republic to the late twentieth century. Some of the contributions in America at the Ballot Box focus on elections that resulted in dramatic political change, including Jefferson's defeat of Adams in 1800, the 1860 election of Lincoln, and Reagan's 1980 landslide victory. Others concentrate on contests whose importance lies more in the way they illuminate the broad, underlying processes of political change, such as the corruption controversy of Cleveland's acrimonious election in 1884 or the advent of television advertising during the 1952 campaign, when Eisenhower defeated Stevenson. Another set of essays takes a thematic approach, exploring the impact of foreign relations, Anglophobia, and political communications over long periods of electoral time. Uniting all of the chapters is the common conviction that elections provide a unique vantage point from which to view the American political system. Ranging from landmark contests to less influential victories and defeats, the essays by leading political historians seek to rehabilitate the historical significance of presidential elections and integrate them into the broader evolution of American government, policies, and politics. Contributors: Brian Balogh, Gareth Davies, Meg Jacobs, Richard R. John, Kevin M. Kruse, Jeffrey L. Pasley, Andrew Preston, Elizabeth Sanders, Bruce J. Schulman, Jay Sexton, Adam I.P. Smith, Sean Wilentz, Julian E. Zelizer.